Evidence for a modulating effect of transcutaneous auricular vagus nerve stimulation (taVNS) on salivary alpha-amylase as indirect noradrenergic marker: a pooled mega-analysis - Giraudier, Manon; Ventura-Bort, Carlos; Burger, Andreas M.; Claes, Nathalie; D'Agostini, Martina; Fischer, Rico; Franssen, Mathijs; Kaess, Michael; Koenig, Julian; Liepelt, Roman; Nieuwenhuis, Sander; Sommer, Aldo; et al. (Brain stimulation, 2022)
Background - Non-invasive transcutaneous auricular vagus nerve stimulation (taVNS) has received tremendous attention as a potential neuromodulator of cognitive and affective functions, which likely exerts its effects via activation of the locus coeruleus-noradrenaline (LC-NA) system. Reliable effects of taVNS on markers of LC-NA system activity, however, have not been demonstrated yet. - Methods - The aim of the present study was to overcome previous limitations by pooling raw data from a large sample of ten taVNS studies (371 healthy participants) that collected salivary alpha-amylase (sAA) as a potential marker of central NA release. - Results - While a meta-analytic approach using summary statistics did not yield any significant effects, linear mixed model analyses showed that afferent stimulation of the vagus nerve via taVNS increased sAA levels compared to sham stimulation (b = 0.16, SE = 0.05, p = 0.001). When considering potential confounders of sAA, we further replicated previous findings on the diurnal trajectory of sAA activity. - Conclusion(s) - Vagal activation via taVNS increases sAA release compared to sham stimulation, which likely substantiates the assumption that taVNS triggers NA release. Moreover, our results highlight the benefits of data pooling and data sharing in order to allow stronger conclusions in research.
Gesehen am 30.01.2023